CAB Abstracts - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Two new CAB Abstracts on CD-ROM are now available. The 1990-91 Volume 3A is a new format and 1992 Volume 3B contains new information. These comprehensive international research databases cover agriculture in its broadest sense including subjects...